The Vote of the Young People. Political Choice of the Young Bulgarians (2009 – 2021) - Iankov, Kaloian (Research Papers, 2022)
The article presents a research on the trends in the political choice of young Bulgarians aged 18-30. The research method is secondary analysis of data from electoral surveys – exit polls and official results of the parliamentary elections in 2009-2021 according to data from the Central Election Commission (CEC). At the first level, the results show who young people are voting for and whether their political choices shift in 2009-2021. At the second level – what is the share of young people among voters’ turnout and among party electoral groups. At the third level, it is possible to see the extent to which the young voter is represented in parliament in the Bulgarian National Assembly.
Keywords: Young people; Parliamentary elections; Political elections; Exit polls